The Silver way : techniques, tips, and tutorials for effective character design - Silver, Stephen, 1972- ([Los Angeles, CA] : Design Studio Press, 2017)
He Silver Way: Techniques, Tips and Tutorials for Effective Character Design by Stephen Silver offers invaluable instruction from one of best teachers in the industry. Whether youre a professional artist interested in improving your drawing skills, or an aspiring designer fresh out of high school looking to add to your portfolio, The Silver Way will help you build your confidence and strengthen your work in order to successfully design characters for any project, in any style. Chockfull of helpfuland entertaining!drawing techniques and easy-to-follow tutorials developed through his decades of experience as an artist on popular animated shows (Kim Possible, Danny Phantom, The Fairly OddParents) and as the owner of Silver Drawing Academy, The Silver Way is the kind of educational art book youll revisit again and again for guidance, encouragement, and inspiration.
Includes index.
Keywords: Cartooning -- Technique; Figure drawing -- Technique